URGENSI PENERAPAN BAHASA ARAB DI PONDOK PESANTREN MODREN TAAJUSSALAAM BESILAM BABUSSALAM TANJUNG PURA LNGKAT TA. 2019-2020 - Zainal Arifin; Sri Rezki (Jurnal Sabilarrasyad, 2021)
This research aims to: 1) Knowing the methods of habituation of Arabic to the students; 2) Know the supporting factors of Arabic; 3) Know the obstacles in the application of Arabic in PPM Taajussalaa. This research method uses qualitative descriptive. The results of this study showed that the implementation of muhadaroh, muhadasah, and mufrodat is very helpful in the process of applying Arabic in pesantren in accordance with the rules that have been taught to students. The role of santri parenting that ensures the application of Arabic runs smoothly in accordance with the expectations and objectives of the language section